Individual and Household Predictors of Adolescents' Adherence to a Web-Based Intervention. Issue 3 (1st October 2014) - Mâsse, Louise C.; Watts, Allison W.; Barr, Susan I.; Tu, Andrew W.; Panagiotopoulos, Constadina; Geller, Josie; Chanoine, Jean-Pierre
Abstract: Background: Adherence to e-health obesity interventions is a significant challenge. Purpose: We examined the individual and household predictors of adolescents' adherence to a Web-based lifestyle intervention. Methods: One hundred sixty overweight/obese adolescents and one of their parents enrolled in the 8-month e-health intervention. Structural equation modeling was used to examine individual factors from the theory of planned behavior and self-determination theory and household factors (food/soda availability, parenting, environment) that predict adolescents' adherence to components of the intervention. Results: We explained 10.8 to 36.9 % of the total variance in adherence to components of the intervention. Intrinsic motivation and parenting practices and styles directly predicted adherence. Relatedness and autonomy support indirectly predicted adherence via intrinsic motivation. Finally, household income modulated these effects. Conclusion: Taking a self-regulatory perspective (i.e., accounting for intrinsic motivation) contributes to our understanding of intervention adherence, but the household environment may play a greater role in facilitating adolescent behavior change.